(Pr0.75Ce0.25)-Fe-B hot-deformed magnets for cryogenic applications. (15th March 2021) - Tang, Xin; Lai, Jiawei; Sepehri-Amin, H.; Ohkubo, T.; Hono, K.
Abstract: We explored the possibility of Pr-Fe-B and (Pr0.75 Ce0.25 )-Fe-B based hot-deformed magnets as magnetic field source for cryogenic magnetic refrigeration. Thanks to the elimination of spin reorientation effect in the rare earth (RE)-Fe-B system, Pr-Fe-B based hot-deformed magnet shows a large remanence of µ0 M r = 1.75 T with a coercivity of 7.4 T at 20 K. To our surprise, (Pr0.75 Ce0.25 )-Fe-B based hot-deformed magnet shows even higher remanence of 1.76 T with a coercivity of 4.8 T at 20 K. The measured maximum energy product of the anisotropic (Pr0.75 Ce0.25 )-Fe-B hot-deformed magnets is 612 kJ/m 3 at 20 K, demonstrating their potential as a low-cost permanent magnet for cryogenic applications. Graphical abstract: Image, graphical abstract